Phase II pilot study of the prednisone to dexamethasone switch in metastatic castration-resistant prostate cancer (mCRPC) patients with limited progression on abiraterone plus prednisone (SWITCH study). Issue 9 (30th October 2018) - Romero-Laorden, Nuria; Lozano, Rebeca; Jayaram, Anuradha; López-Campos, Fernando; Saez, Maria; Montesa, Alvaro; Gutierrez-Pecharoman, Ana; Villatoro, Rosa; Herrera, Bernardo; Correa, Raquel; Rosero, Adriana; Pacheco, María; et al.
Abstract Background Despite most metastatic castration-resistant prostate cancer (mCRPC) patients benefit from abiraterone acetate plus prednisone 5 mg bid (AA + P), resistance eventually occurs. Long-term use of prednisone has been suggested as one of the mechanisms driving resistance, which may be reversed by switching to another steroid. Methods SWITCH was a single-arm, open-label, single-stage phase II study. The primary objective was to evaluate the antitumour activity of abiraterone acetate plus dexamethasone 0.5 mg daily (AA + D) in mCRPC patients progressing to AA + P. Clinically stable mCRPC patients who had prostate-specific antigen (PSA) and/or limited radiographic progression after at least 12 weeks on AA + P, were eligible. The primary endpoint was measured as the proportion of patients achieving a PSA decline of ≥ 30% (PSA30) from baseline after 6 weeks on AA + D. Secondary endpoints included: PSA50 response rate at 12 weeks, time to biochemical and radiological progression, overall survival, safety profile evaluation, benefit from subsequent treatment lines and the identification of biomarkers of response (AR copy number, TMPRSS2-ERG status and PTEN expression). Results Twenty-six patients were enrolled. PSA30 and PSA50 were 46.2% and 34.6%, respectively. Median time to biochemical and radiological progression were 5.3 and 11.8 months, respectively. Two radiological responses were observed. Median overall survival was 20.9 months. Patients withAR gain detected in plasma circulating tumour DNA did not respond to switch, whereas patients withAR normal status benefited the most. No significant toxicities were observed and PSA50 response rate to subsequent taxane was 50%. Conclusions In selected clinical stable mCRPC patients with limited disease progression on AA + P, a steroid switch from prednisone to dexamethasone can lead to PSA and radiological responses.